Training on Strategies for Reading Printed and Digital Texts for Students of MTs Mahdaliyah, Jambi City - Melati; Nyimas Triyana Safitri; Radiatan Mardiah; Nely Arif; Duti Volya (Jurnal Karya Abdi Masyarakat, 2026)
This community service activity aimed to provide training on strategies for reading printed and digital texts to increase students’ interest in reading. Based on the results of research conducted by the community service team in the previous year, several different strategies for reading these two types of texts were identified. Therefore, it was considered necessary to disseminate these strategies to the target users, namely junior high school students. Increasing students’ interest in reading beneficial texts is important because reading activities today are increasingly challenged by the presence of digital devices that offer various forms of entertainment, such as games, social media, and other content. During the implementation of the activity, the community service team provided materials on the importance of reading, why students should engage with various types of media, and different types of beneficial reading materials in both digital and printed formats, along with other mentoring activities. By becoming more familiar with reading activities and strategies, it is expected that students will develop greater interest in reading and improve their reading skills.